Compositional modelling and crushing behaviour of MSWI bottom ash material classes. (1st January 2020) - van de Wouw, P.M.F.; Loginova, E.; Florea, M.V.A.; Brouwers, H.J.H.
Graphical abstract: Highlights: Distinct physical and chemical properties of MSWI BA classes were determined. Magnetic separation of ferrous containing slag is suggested for beneficiation. The proposed model enables the calculation of a MSWI BA class composition. The behaviour of MSWI BA classes during crushing was determined using the model. Selective crushing of MSWI BA is found applicable for material class beneficiation. Abstract: At present, in Europe, 18 million tonnes of MSWI Bottom Ash (BA) is annually stockpiled or used in low-grade applications (e.g. in road bases). Therefore, alternative applications, such as aggregate or as a cement component in concrete, are stimulated. Physical and chemical characteristics remaining after treatment, however, prevent its extensive application in building materials. Hence, knowledge is needed on the distinct properties of the material classes making up a heterogeneous BA, enabling the assessment of its characteristics and the resulting applicability. Furthermore, a user-friendly composition assessment procedure is necessary to evaluate the output of physical treatment processes. Crushing is a commonly applied treatment and its effect on the material classes comprising BA is still unknown. In this paper, the latter are identified and classified into slag, magnetic slag, glass, refractory, metals, and unburned material classes. The individual characteristics of each material class are identified and a suitable tracer for tracking these classes in heterogeneous samples is defined. Furthermore, a fast method to quantify the distribution of material classes based just on the oxide composition is developed and applied to approximate the changes in the configuration of BA through crushing. It is concluded that, although the jaw crushing of BA results in a more homogeneous distribution, beneficiation of material classes occurs and selective crushing is possible in order to improve the quality of the BA and therefore its subsequent application.